AKTIVITAS ANTIMIKROBA KOMBINASI EKSTRAK PROPOLIS Trigona sp DAN JAHE (Zingiber officinale ROSCOE) TERHADAP BAKTERI Salmonella thypimurium - Muhammad Fadhlullah Mursalim; Abdul Wahid Jamaluddin (Fakultas Farmasi UMI, 2019)
This study aims to find the antimicrobial activity of a combination of extract propolis Trigona sp and gingger (Zingiber officinale var ROSCOE) against Salmonella thypimurium. The test was carried out by the method of diffusion disc with propolis and ginger test material. The study was conducted with 10 groups treatment, namely the combination of K1 (1mL ginger (30%)), K2 (1mL ginger (30)% & 1mL propolis (1%)), K3 (Ginger 1 mL (30%) & propolis 1 mL (5% ), K4 (1mL ginger (15%)) K5 (1mL ginger (15%) & 1mL propolis (1%)), K6 (1mL ginger (15%) & 1 mL propolis (5%)), K7 (1 mL propolis 1 %), K8 (1 mL propolis 5%), negative control K9 (DMSO 10%), and K10 (positive control amoxicillin). The results showed that the combination extract of propolis and ginger on K3 had the highest inhibition area of Salmonella thypimurium 12.26 mm. This study proves that various combinations of concentrations of propolis and ginger extract have antibacterial activity against the growth of Salmonella typhimurium.